Anal cancer with large metastases into the perirectal fat: differential diagnosis and treatment policy - A. O. Rasulov; S. S. Gordeev; V. A. Ivanov; S. I. Tkachyоv; V. V. Glebovskaya; Yu. E. Suraeva; S. S. Balyasnikova (Тазовая хирургия и онкология, 2016)
Selected squamous-cell anal carcinoma (SCAC) patients are initially presented with large pararectal lymph node metastases.The aim of this study was to investigate safety, efficacy and long-term outcome of chemoradiotherapy in this patient group.Materials and methods. SCAC patients, initially referred with gastrointestinal stromal tumors, rectal cancer diagnosis or patients with regional metastatic lymph nodes more than twice the size of the primary tumour were included in this retrospective analysis. Previous treatment, diagnostic and clinical mistakes of primary care specialists, short- and long-term outcome of chemoradiotherapy were analyzed.Results. 6 patients were included. Primary tumour size varied between 0.5 and 6.5 cm (median – 1.7 cm), metastatic lymph node size varied between 4.2 and 7.4 cm (median – 6.4 cm). All patients received radical doses of chemoradiation. All patients developed grade 3 toxicities, 2 patients developed grade 4 toxicities. Median followup was 15.5 months. 5 out of 6 patients had persistent complete clinical response. 1 patient died of disease progression (incomplete response and metachronous distant metastases).Conclusion. SCAC patients with large regional lymph node metastases have equal prognosis with the rest of the patient group of adequate treatment was carried out.